Manajerial Kepala Sekolah Dalam Pemanfaatan Beasiswa Terhadap Peningkatan Kualitas Pendidikan - Nahroji Nahroji; Muhammad Anas Ma’arif; Ari Kartiko; Freddrick Tiagita Putra (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2023)
This research was held. What is the managerial influence of the school principal on the quality of education, and the provision of scholarships on the quality of existing education? This research took place at Al Amien Jatigunting Middle School, Wonorejo District, Pasuruan Regency. n In conducting the research, researchers used qualitative research methods with case studies to see the extent to which the managerial influence of school principals and scholarships had on the quality of education in Al Amien Middle School. Documentation, interviews, and observations are the steps of the researcher in obtaining accurate data to be presented as a result of the research. In addition, the researcher also took some data as a reference for the results of the research that will be carried out later. In addition to data, the researchers also took some documentation as supporting evidence for the results of the research that will be presented. The results of this study are 1) there is managerial influence on improving the quality of education, including the management of teachers and education staff who lack discipline 2) lack of facilities and infrastructure existing infrastructure at the institution, so that students have to study at other institutions 3) scholarships are sufficiently capable of attracting many students to study at this institution with the waiver of school fees, as well as the cost of school uniforms.